Florinetta and the Food of Freedom: Morgante XIX - Palma, Pina (Table talk. Perspectives on food in medieval Italian literature, 2010)
Keywords: dept.wll

Futurist arte / vita: Benedetta Fictionalized - Larkin, Erin (Volume 8 2018, 2018)
Keywords: dept.wll

Faunos en los trópicos: modernismo y virilidad - Hernández Rodríguez, Rafael (Ecos y resplandores helenos en la literatura hispana: siglos XVI-XXI, 2018, ISBN 978-84-697-9697-9, págs. 113-130, 2018)
Modernism represents an artistic movement that mirrors the changing society of the late 19th century. This changing society produced the first cultural and artistic movement in Spanish America that asked what was this region's place in the Western World as well as what the poet's new function was. Among other issues that revea) the modernity of the movement, such as urbanization, industrialization, or the role of women, there is one of capital importance: the view of masculinity. This essay focuses on three texts that review the image of masculinity and art thought the figure of the faun. El modernismo representa un movimiento artístico que refleja la sociedad cambiante de finales del siglo XIX. Esta sociedad cambiante genera el primer movimiento cultural y artístico continental de importancia que intenta responder a la pregunta ¿cuál es el lugar de Hispanoamérica en el mundo occidental y cuál es la nueva función del poeta? Entre otros aspectos que señalan la modernidad del movimiento (como el urbanismo, la industrialización, el papel de la mujer), hay uno de particular importancia: la revisión de la masculinidad. Este ensayo se centra en tres textos que revisan la visión de la masculinidad y el arte a través de la imagen del fauno.
Keywords: dept.wll

Symbolic Violence and Public Displays of Difference - Compan, Magali (Visualizing Violence in Francophone Cultures, 2015)
Visualizing Violence in Francophone Cultures brings together two complex and powerful loci of meaning: violence and the visual. As such, it offers a comprehensive overview from which one can gain a better understanding of the complexity of the visual rhetoric of violence. The visual representations of violence explored in this volume include both fictional works, including, for example, narrative films, graphic novels, and theatre, and non-fictional genres, such as news media and cultural artifacts. This volume’s strength is also grounded in its interdisciplinary approach; by bringing together scholars from a variety of academic fields to examine a broad range of visual artifacts, such as photography, graphic novel, films, paintings, objects, the book offers a substantive corpus focusing on the rhetoric of violence. The essays collected in this volume explore the ways in which visual expressions of violence have infiltrated diverse narrative forms, and, as such, how they both construct and challenge general understandings of contemporary violence. They all chart, with cultural and historical specificity, the way in which images of violence shape the visual imaginary of ethical worlds.
Keywords: History / General; dept.wll

Communicative relevance: Color references in bilingual and trilingual speakers - Pavlenko, Aneta; Jarvis, Scott; Melnyk, Svitlana; Sorokina, Anastasia (Bilingualism: Language and Cognition, 2017)
The study examined granularity of lexical partitioning of the blue area in speakers of English, which encodes the term blue; Russian, which encodes two terms, sinij [dark/navy blue] and goluboj [light/sky blue]; and Ukrainian, which encodes the terms synij [dark/navy blue] and blakytnyj and golubyj [light/sky blue]. Five groups of participants took part in the study: (1) 30 L1 speakers of English, (2) 30 L1 speakers of Russian, (3) 30 Russian–English bilinguals, (4) 30 English–Russian bilinguals, and (5) 25 Ukrainian–Russian–English trilinguals. Quantitative and qualitative analyses revealed that L1 Russian speakers referred to different types of blue significantly more frequently than all other groups, while bilinguals patterned with L1 English speakers. These findings suggest that classroom exposure to L2 Russian does not make the distinction between sinij and goluboj communicatively relevant for L1 English speakers and that everyday use of L2 English may trigger attrition of the contrast in L1 Russian.
Keywords: Russian; bilingual lexicon; color; communicative relevance; crosslinguistic influence; dept.wll

Crimean crisis of 2014 in the conservative and liberal U.S. media - Sorokina, Anastasia N. (Russian Journal of Communication, 2017)
Keywords: Crimean crisis; U.S. media; critical discourse analysis; dept.wll; transitivity

Report for Sabbatical Leave, Spring 2011. - Piemontese, Luisa (2011)
Studied contemporary poetry in Spanish by Spanish-speaking authors living in Connecticut. Works of four poets were chosen for a bilingual anthology. Seventy five percent of poems selected for this publication were translated and their analytical study completed. In addition, audio interviews were completed, and multimedia presentation, including photos, biographies, and bilingual readings was compiled and given. Publishing companies were identified for submission of the anthology's proposal.
Keywords: Connecticut; Poets, Spanish American; United States; dept.wll; faculty_collection; sabbatical_report

Alsace and the French territorial debate: shifting the borders and discourses of regional and national identity - Eilderts, Luke L. (2019)
Keywords: dept.wll; faculty_collection; sabbatical_report

The Minor Tone of Desire - Barros, Pía; Cardone, Resha (Ediciones Sherezade, 2018)
Keywords: 21st century; Chilean fiction; Translations into English; Translations into English; Chilean fiction; Women authors; dept.wll; faculty_collection

De Connecticut a Salamanca: SCSU Program in Spain, 1990-2015, 25 Years of International Education Making a Difference - Arboleda, Carlos Arturo (Southern Connecticut State University, 2016)
Keywords: Connecticut; Southern Connecticut State University; International education; Spain; International education; dept.wll; faculty_collection

Sabbatical Leave Report. - Latorre, Sobeira (2015)
The objective of my sabbatical leave was to make progress on a book project tentatively entitled: "In conversation: Dominican women writers speak." This project is a book of interviews with contemporary women writers from the Dominican Republic as well as writers who identify themselves as Domincan-American...
Keywords: dept.wll; faculty_collection; sabbatical_report

Unbound and Underground: Chile's Ergo Sun Project from the Dictatorship to the Digital Era - Cardone, Resha (2014)
Cardone wrote chapters of a book manuscript and submitted two related articles to peer reviewed journals. She also transcribed and edited a scholarly interview, presented portions of book project at conference and traveled to site of book topic for on-ground research. Accomplishments are different than outlined in original proposal. The report describes project issues and results.
Keywords: dept.wll; faculty_collection; sabbatical_report

The Origins of Western Law from Athens to the Code Napoleon - Ecklund, John E. (Talbot Publishing, 2014)
Keywords: Europe; History; Law, Ancient; Law, Medieval; Law; dept.wll; faculty_collection; sabbatical_report

Modern Italian theater: (from Praga to Sciascia : text and context) - Vena, Michael (Xlibris LLC, 2014)
Keywords: 19th century; Theater; 20th century; Italy; Theater; dept.wll; faculty_collection

Italian Playwrights from the Twentieth Century: A Companion Text - Vena, Michael (Xlibris Corporation, 2013)
Keywords: 20th century; History and criticism; Italian drama; dept.wll; faculty_collection

Los Que Sobran = Those Not Spared - Barros, Pía (Colección Escrito en el agua, 2010)
Keywords: 21st century; 21st century; Chilean fiction; Chilean fiction; Translations into English; Translations into English; Chilean fiction; Women authors; Women authors; Chilean fiction; dept.wll; faculty_collection

A Revolution of Shadows: Culture and Representation in Early-Twenieth-Century Mexico - Hernández Rodríguez, Rafael (The Popular Avant-Garde, 2010)
The avant-garde has been popular for some time, but its popularity has tended to fly under the radar. This “popular avant-garde,” conceived as the meeting ground of the avant-garde and popular, avoids the divorce of art and praxis of which the avant-garde has been accused. The Popular Avant-Garde takes stock of the debates about both the “historical” (“modernist”) and posterior avant-gardes, and sets them in relation to popular culture and art forms. With a critical introduction that examines the concepts of “the avant-garde,” “the popular,” and “the popular avant-garde,” the series of essays analyzes the way in which the avant-garde employs popular genres for political purposes, as well as how the popular acquires a critical function with respect to the avant-garde. Each of the volume’s three sections considers a different aspect of the productive exchange between the avant-garde and popular: the popular avant-garde as a culturally hybrid and cross-border phenomenon; the play between the popular avant-garde and developments in media and technology; and the popular avant-garde’s upending of conventional ideas about “the people” and “the popular.” The Popular Avant-Garde takes a fresh look at the now canonical Dadaist, Futurist, and Surrealist movements from the perspectives of gender and sexuality, and cultural and critical theory, while at the same time exploring less well-known avant-garde work in literature, film, television, music, photography, dance, sculpture, and the graphic arts. This volume’s coverage of the American and Afro-American, Luso-Brazilian and Latin-American, East-European, and Scandinavian avant-gardes, in addition to the vanguards of Spain and other parts of Western Europe, will appeal to all those interested in avant-garde and popular art forms.
Keywords: Avant-garde (Aesthetics); Popular culture; dept.wll; faculty_collection

Sabbatical leave report: Fall 2014 - Cardone, Resha (2014)
Cardone wrote chapters of a book manuscript and submitted two related articles to peer reviewed journals. She also transcribed and edited a scholarly interview, presented portions of book project at conference and traveled to site of book topic for on-ground research. Accomplishments are different than outlined in original proposal. The report describes project issues and results. Book title is "Unbound and underground: Chile's Ergo Sun Project from the dictatorship to the digital era."
Keywords: dept.wll; faculty_collection; sabbatical_report

Why did the monkey kill the giant? Another look at Margutte's death - Palma, P. (Quaderni d'Italianistica, 2010)
In the Morgante through Margutte's death-by-laughter Pulci voices a caustic critique of Ficino's philosophical theories while obliquely denouncing Lorenzo de Medici's acceptance of them. The spectacle of the monkey wearing and taking off Margutte's boots follows Aristotle's definition of the ridiculous that ignites hilarity. It also retrieves Bergson's idea of a society that can be derided because of its attempts to disguise its true self. Most importantly, it reintroduces Petrarch's concepts of similitudo and identitas. Through the depiction of the giant's death Pulci reveals the dignity of a poet remaining true to his poetic discourse even while coming to terms with the negative turn his career has taken.
Keywords: dept.wll

Jews and Jewishness in Carme Riera‘s Dins el darrer blau - Sosa-Velasco, A.J. (Iberian Modalities: A Relational Approach to the Study of Culture in the Iberian Peninsula, 2010)
Las hogueras del fanatismo y la ortodoxia son una constante del siglo XXI, en el que ya estamos. Seguimos proyectando nuestro peor yo sobre los débiles, los pobres y los emigrantes. Necesitarí amos matar el yo racista que llevamos dentro y eso sólo se puede conseguir colocándonos en el lugar del otro, sintiéndote agredida. In the last twenty-five years, Jews have emerged as a literary figure as well as a literary theme in Spain. Catalan writers such as Maria Àngels Anglada (1930- 99), Carme Riera (1948–), and Vicenç Villatoro (1957–) approach the Jewish theme and the representation of the Jew as literary character in order to reflect on issues regarding identity and history in novels, such as El violí d‘Auschwitz (1994), Dins el darrer blau (1994), and Memòria del traïdor (1996), respectively. With Dins el darrer blau, written between 1989 and 1993, published in Catalan in 1994 and in Castilian in 1996, Riera starts a series of novels dedicated to the Majorcan xuetes (Jews who were converted to Christianity) which she finishes with Cap al cel obert in 1999. In this essay I will reflect on how Riera‘s Dins el darrer blau revisits the past in order to create a “culture of memory,” a process in which society confronts its traumatic past and the history of exile and repression, linking the history of the Jewish converts to the history of the Balearic island, Majorca. Riera‘s novel is based on historical events that occurred in the City of Majorca from 1687 to 1691. © 2013 Liverpool University Press.
Keywords: dept.wll

Refashioning the book in Pinochet's Chile: The feminist literary project. Ergo Sum - Cardone, R. (Confluencia, 2013)
Keywords: dept.wll; ⛔ No DOI found

Savoring Power, Consuming the Times: The Metaphors of Food in Medieval and Renaissance Italian Literature - Palma, Pina (University of Notre Dame Press, 2013)
"Pina Palma's Savoring Power, Consuming the Times: The Metaphors of Food in Medieval and Renaissance Italian Literature is an innovative look at the writings of five important Italian authors--Boccaccio's Decameron, Pulci's Morgante, Boiardo's Innamorato, Ariosto's Furioso, and Aretino's Ragionamento. Through the prism of gastronomy, Palma examines these key works in the Western literary canon, bringing into focus how their authors use food and gastronomy as a means to critique the social, political, theological, philosophical, and cultural beliefs that constitute the fabric of the society in which they live." -- Publisher's website.
Keywords: 16th century; History and criticism; Food in literature; Gastronomy in literature; History and criticism; Italian literature; Italian literature; SCSU Faculty Scholar Award; To 1400; award_winner; dept.wll; faculty_collection

Fairness - Scott Walters, F. (The Routledge Handbook of Language Testing, 2013)
Among language testing researchers, the notion of fairness has accumulated a number of complex, technical definitions over the years. However, since the word has such a widespread, everyday usage, consulting a dictionary can be a good starting-point for discussion. For example, YourDictionary.com (2011) states that to be fair is to be “just and honest,” “impartial,” and “unprejudiced,” specifically, “free from discrimination based on race, religion, sex, etc.“Merriam-Webster (Mish et al., 2003) states similarly that fairness is “marked by impartiality or honesty” and is “free from self-interest, prejudice, or favoritism.” As this volume deals with second/foreign/other language testing, it would seem appropriate (or perhaps one should say, fair) to include a dictionary definition crafted for L2 learners, as is this one from Cambridge (Walter et al., 2006): “Treating someone in a way that is right or reasonable, or treating a group of people equally and not allowing personal opinions to influence your judgment.”. © 2012 Selection and editorial matter, Glenn Fulcher and Fred Davidson.
Keywords: dept.wll

Shifting paradigms: A model for the integrated assessment of language and culture - Hammer, J.; Schmitt, E. (Culture and Foreign Language Education: Insights from Research and Implications for the Practice, 2015)
Keywords: dept.wll

Satire, ecocentrism, and luddite discourse in One Hundred Years of Solitude: regional approaches for a global environmental crisis - Flores, William (Gabriel García Márquez in Retrospect: A Collection, 2016)
Gabriel Garcia Marquez in Retrospect gathers fifteen essays by noted scholars in the fields of Latin American literature, politics, and theater. The volume offers broad overviews of the Colombian author’s total body of work, along with closer looks at some of his acknowledged masterpieces. The Nobel laureate’s cultural contexts and influences, his variety of themes, and his formidable legacy (Hispanic, U.S., world-wide) all come up for consideration. New readings of One Hundred Years of Solitude are further complemented by fresh, stimulating, highly detailed examinations of his later novels (Chronicle of a Death Foretold, The General in His Labyrinth, Of Love and Other Demons) and stories (Strange Pilgrims). Further attention is focused on “Gabo’s” labors as journalist and as memoirist (Living to Tell the Tale), and to his sometime relationships with the cinema and the stage. Reactions to his enormous stature on the part of younger writers, including recent signs of backlash, are also given thoughtful scrutiny. Feminist and ecocritical interpretations, plus lively discussions of Gabo’s artful use of humor, character’s names, and even cuisine, are to be found here as well. In the wake of García Márquez’s passing away in 2014, this collection of essays serves as a fitting tribute to one of the world’s greatest literary figures of the twentieth century.
Keywords: Literary Criticism / Caribbean & Latin American; Literary Criticism / General; Literary Criticism / Modern / 20th Century; dept.wll

Ecocrítica Poscolonial Y Literatura Moderna Latinoamericana - Flores, William (Universidad Nacional Mayor de San Marcos, Fondo Editorial, 2015)
Keywords: 21st century; History and criticism; Ecocriticism; Latin America; Ecocriticism in literature; Postcolonialism in literature; Environmentalism in literature; Ecology in literature; Latin American fiction; dept.wll; faculty_collection

Queering the public sphere in mexico and brazil: sexual rights movements in emerging democracies by rafael de la dehesa - Hernández-Rodríguez, R (The Latin Americanist, 2011)
Keywords: dept.wll; peer-reviewed

Book Review: Constructing the image of the mexican revolution: cinema and the archive (review) - Hernández-Rodríguez, Rafael (Americas, 2011)
Keywords: book.review; dept.wll; peer-reviewed

Measuring oral proficiency through paired-task performance - Walters, F. Scott (The Modern Language Journal, 2011)
Keywords: dept.wll

Inventing the self, fictionalizing the other: false memories in the theatre of mario vargas llosa - Melendez, Priscilla (Symposium: A Quarterly Journal in Modern Literatures, 2012)
The Peruvian writer Mario Vargas Llosa, one of the most prolific and distinguished Spanish American novelists of the twentieth century and the winner of the 2010 Nobel Prize in Literature, is also the author of eight plays, which have frequently been overshadowed by his narrative production. Going beyond the relationship traced by critics between his novels and his plays, this essay underscores the prevalence in his theatrical work of a tug of war between biographical and autobiographical voices as part of a fundamental exploration of real and fictional memory. From Vargas Llosa's early plays of the 1980s to his most recent ones, he has frequently dramatized the life of both real and imaginary, famous and infamous others and selves, creating the illusion that the audience is witnessing someone's life trajectory. This is the analytical angle from which this essay approaches not only Vargas Llosa's first play, La seorita de Tacna (1981), but in particular one of his most recent ones, Odiseo y Penélope (2007). In both analyses, the definitions of biographical and autobiographical discourses are interpreted in light of theatrical representation, underscoring in this way the subjective, dramatic, and metaphorical perspectives of these expressions. © 2012 Taylor and Francis Group, LLC.
Keywords: La seorita de Tacna; Odiseo y Penélope; Vargas Llosa; autobiography; dept.wll; theatre

A remecer consciencia en Chile y en el extranjero: una conversación con Pía Barros sobre las antologías ¡Basta! - Cardone, Resha Sophia (A Contracorriente: Revista de Historia Social y Literatura en América Latina, 2013)
Keywords: dept.wll; ⛔ No DOI found

Students in the new millennium: how much do we know about them? - Wu, Jianxiong (Computer-Assisted Foreign Language Teaching and Learning: Technological Advances, 2013)
Vast and fast technological advancements mark the new millennium. New emerging technologies are changing the world and our society at a magnitude and scope never witnessed before. Who are our students in this new millennium? What do they look like? Are they a fundamentally different new generation as some claim, or do they still look similar to us in many ways? A clear understanding of the characteristics of our students is vitally important for our educational practice. The current study was conducted to contribute to this understanding. The findings of the study show that while students nowadays do enjoy a much broader access to new technology than students of the past, they still look similar to us in many ways. As educators, it is important for us to treat our students as individuals instead of just labeling them and placing them in a black and white dichotomy.
Keywords: Emerging technologies; Students; Technological advancement; Technology transfer; dept.wll

María Elena Gertner: Conversación en torno a la literatura - Cardone, Resha Sophia (Revista Chilena De Literatura, 2016)
Keywords: dept.wll

Book Review: Art beyond itself: anthropology for a society without a story line. by néstor garcía canclini. trans. david frye. durham: duke university press, 2014, p. 201, 23.95. - Cardone, Resha Sophia (The Latin Americanist, 2015)
Keywords: book.review; dept.wll

Nona fernández's mapocho: spirits in a material wasteland - Cardone, Resha Sophia (Studies in Twentieth-and Twenty-First Century Literature, 2015)
Keywords: dept.wll

Book Review: Masculinity after trujillo: the politics of gender in dominican literature. by maja horn. gainesville: university press of florida, 2014, p. 202, 69.95. - Latorre, Sobeira (The Latin Americanist, 2015)
Keywords: book.review; dept.wll

Meaning-based scoring: A systemic functional linguistics model for automated test tasks - Gleason, Jesse (Hispania-a Journal Devoted to the Teaching of Spanish and Portuguese, 2014)
Communicative approaches to language teaching that emphasize the importance of speaking (e.g., task-based language teaching) require innovative and evidence-based means of assessing oral language. Nonetheless, research has yet to produce an adequate assessment model for oral language (Chun 2006; Downey et al. 2008). Limited by automatic speech recognition (ASR) technology, which compares non-native speaker discourse to native-like discourse, most tests exclusively focus on accuracy while ignoring how examinees use language to make meaning. In order to offer stakeholders more trustworthy evidence of how examinees might use language in target language domains, a model anchored in systemic functional linguistics (SFL) is put forth. Specific examples are given of how SFL might be used to evaluate test task types, such as the story retell:three examinees' responses are contrasted using genre analysis (Derewianka 1990) and transitivity analysis (Ravelli 2000) in order to demonstrate elements in their linguistic profiles that ASR-based assessment would overlook. In so doing, implications are drawn regarding the potential of SFL models for enhancing automated scoring procedures by focusing on the meaning-form relations in the linguistic construction of narrative.
Keywords: Adult Spanish literacy alfabetización adulta de español; Automated language assessment evaluación automática del lenguaje; Discourse analysis análisis del discurso; Systemic functional linguistics lingüística sistémico-funcional; Transitivity analysis análisis de transitividad; dept.wll; peer-reviewed

Using big questions to apprentice students into language-rich classroom practices - Verplaetse, Lorrie Stoops (TESOL Quarterly, 2014)
Keywords: dept.wll

“It helps me get closer to their writing experience” Classroom ethnography and the role of technology in third-year FL courses - Gleason, Jesse (System, 2014)
Research has shown a disjunction between language instruction at the lower and upper levels of foreign language (FL) study. Whereas lower-division courses focus on grammatical patterns, upper-level courses focus on specific content. The third-year writing course is in a unique position to help learners prepare for the types of learning that they will encounter in more advanced language use contexts. Using grounded classroom ethnography, this multiple case study of two classrooms chronicles how a collaborative partnership between an instructor and an applied linguist facilitated the integration of two types of technology into a third-year Spanish writing course at a North American University. Technology was carefully chosen based on pedagogical considerations and teacher goals. Students in these courses included a mixture of heritage and FL Spanish learners with a mean age of 21 years. Findings included four ways that technology played a role in third-year Spanish language learning, including as: (a) a way to alleviate their workloads, (b) a motivator, (c) a way to improve the quality and quantity of feedback students received in the course, and in some cases (d) antagonistic to language learning. Implications of classroom ethnography for research on blended learning are drawn. Published by Elsevier Ltd.
Keywords: Blended language learning; Discourse analysis; Ethnography; Language-content gap; Spanish; Teacher-researcher collaboration; Technology; Third-year FL courses; Writing; dept.wll

Developing cultural humility through critical service learning - Breda, Karen Lucas; Groot, Kim; Towle, Antoinette (Ciencia y enfermería, 2013)
Marked inequities or disparities in health care and health outcomes exist for millions in the United States of America. Urban apartheid and increasing social stratification separate social groups making it difficult for them to understand each other. Many U.S. health care professionals, including nurses, hold negative stereotypes toward the urban poor and disenfranchised. Creating vehicles for understanding and respect between health care professionals and the social groups they care for is needed. Cultural humility uses self-reflection, self-critique, openness and transcendence to address power inequities between providers and clients. "Critical service-learning" is a type of "service-learning" that adopts the tenets of critical theory and pedagogy in engaged partnerships to foster social responsibility and a justice-oriented framework. The purpose of this article is to showcase Project Horizon, an innovative university-based health and social advocacy partnership that uses critical service learning with the urban community to foster cultural humility. Project Horizon outcomes show that this long-term engaged partnership is an effective vehicle for developing and enhancing cultural humility among health care professionals participating in the endeavor. Implications: Replication of social and health advocacy projects such as the one conducted through Project Horizon can be made in other settings to increase the capacity for democratically oriented nurses and other health care professionals who have an enhanced sense of cultural humility.
Keywords: Critical service learning; Cultural humility; Health consortia; Health personnel; Healthcare disparities; dept.wll

The memory of state terrorism in the southern cone: argentina, chile, and uruguay. by FrancescaLessa and VincentDruliolle (eds.). new york: palgrave macmillan, 2011. p. 227, 85.00. - Cardone, Resha Sophia (The Latin Americanist, 2013)
Keywords: dept.wll; peer-reviewed

Benedetta and the creation of ‘Second Futurism’ - Larkin, Erin (Journal of Modern Italian Studies, 2013)
Despite the recent vogue in studies on Futurism, writer and artist Benedetta Cappa Marinetti has received little critical attention. Few scholarly works have focused on her essays regarding woman and the Fascist state, and in particular the role of mother. It has been argued that these texts support not only the position that women futurists - in adhering to a movement remembered for its disprezzo della donna - were victims of their self-accepting inferiority, but also the view that Futurist attitudes towardswomen were a precursor of Fascist-era gender politics. Larkin challenges this position, and discusses crucial new archival research, which reveals how maternity in Benedetta's works is actually linked to her radical new reformulation of Futurism. Far from seconding woman's inferior position within the avant-garde, or indeed the Fascist state, Benedetta uses the issue of maternity subtly to subvert her status - in both the movement and society - from within. © 2013 Taylor & Francis.
Keywords: Avant-garde; Benedetta; Cappa; Futurism; Marinetti; Women writers; dept.wll

Assessing strategic cultural competency: holistic approaches to student learning through media - Hammer, Judith; Swaffar, Janet (The Modern Language Journal, 2012)
The current study investigated the impact of a German television program on changes in 4th-semester German students' reflections on cultural perceptions over the course of 1 semester. Sixty-nine students at the University of Texas at Austin watched 4 episodes of the popular German television program Lindenstrasse. After viewing, students were asked to reflect in written response papers on cultural features and patterns of behavior and on cultural differences and similarities. The study results suggest that students' perceptions of another culture can become more sophisticated when being exposed to authentic filmic material and asked to reflect in writing about observed plot features and cultural manifestations. The key to these results is a strategy for assessing not just students' recall of cultural content, but also their strategic competencies in negotiating cultural difference. Changes in students' cognitive styles were tracked by a scale that rewards students' strategic ability tomanage details of cultural knowledge and sociolinguistic content, including the following categories: (a) rhetorical organization; (b) content; (c) comparative point of view; and (d) interpretive substance. The article provides a model for the assessment of cultural competency (MACC), which can be adapted to assess students' engagement with the culture represented in various materials.
Keywords: dept.wll

Afro-Latino/a identities: challenges, history, and perspectives - Latorre, Sobeira (Anthurium: A Caribbean Studies Journal, 2012)
Keywords: dept.wll

Utopian worlds: vico, la capria and mazzotta - Palma, Giuseppina (MLN - Modern Language Notes, 2012)
Keywords: dept.wll

La luz Y la guerra: el cine de la revolucion mexicana edited by fernando fabio sánchez and gerardo garcía muñoz - Rodriguez, R Hernandez (The Latin Americanist, 2012)
Keywords: dept.wll; peer-reviewed

Mañana forever? Mexico and the mexicans by jorge g. castañeda - Rodriguez, R Hernandez (The Latin Americanist, 2012)
Keywords: dept.wll; peer-reviewed

The bachelet government: conflict and consensus in Post‐Pinochet chile edited by silvia borzutzky and gregory b. weeks - Cardone, Resha Sophia (The Latin Americanist, 2011)
Keywords: dept.wll; peer-reviewed

Bilingualism and Learning - Verplaetse, L. S.; Schmitt, E. (International Encyclopedia of Education (Third Edition), 2010)
Bilingualism is defined as a speaker's ability to use two languages for communication. Due to the complexity of its nature, the study of bilingualism relies on several fields within linguistics, anthropology, psychology, neuroscience, and education. The study of bilingualism describes language behaviors of bilingual speakers, social and pragmatic patterns of using two languages, language development, and acquisition and loss, among other issues. Researchers attempt to explain the effect that bilingualism has on human cognition, societal relationships, and education of bilingual children. This article discusses bilingualism and learning from three perspectives: types of bilingualism, bilingual processing, and bilingualism and academic learning.
Keywords: Academic language; Additive bilingualism; Anomie; Balanced bilingualism; Bilingualism; Code switching; Diglossia; Immersion model; Maintenance bilingual (education); Semilingualism; Sequential bilingualism; Sheltered content (instruction); Simultaneous bilingualism; Societal bilingualism; Subtractive bilingualism; Transitional bilingual (education); dept.wll

When boundaries are crossed: Evaluating language attrition data from two perspectives - Schmitt, Elena (Bilingualism: Language and Cognition, 2010)
This study provides an account for a long-term selective loss of L1 (Russian) morpho-syntactic and content components in early immigrants to the US. The analysis of naturally occurring data is carried out from the perspective of two theoretical approaches - three models developed within language contact (Myers-Scotton 2002, 2005) and the Activation Threshold hypothesis as a component of a neurolinguistic approach to bilingualism (Paradis, 2004, 2007). The results show that the language contact approach is useful in identifying morpheme types that are most vulnerable to attrition. The second approach helps explain the differential rate of loss of content morphemes in a variety of topics and account for variability in the rate of attrition of late system morphemes through frequency factors. The study demonstrates that by crossing the boundaries of one theory, and one view of language researchers can achieve a stronger explanatory power and identify the common and complementary features that both models provide.
Keywords: dept.wll

Brazil, lyric, and the americas by charles a. perrone - Rodriguez, R Hernandez (The Latin Americanist, 2010)
Keywords: dept.wll; peer-reviewed

Gender and the mexican revolution: yucatán women and the realities of patriarchy by stephanie j. smith - Rodriguez, R Hernandez (The Latin Americanist, 2010)
Keywords: dept.wll; peer-reviewed

Morphological attrition - Schmitt, Elena (The Oxford Handbook of Language Attrition, 2019)
This volume is the first handbook dedicated to language attrition, the study of how a speaker's language may be affected by crosslinguistic interference and non-use. The effects of language attrition can be felt in all aspects of language knowledge, processing, and production, and can offer unique insights into the mind of bilingual language users. In this book, international experts in the field explore a comprehensive range of topics in language attrition, examining its theoretical implications, psycho- and neurolinguistic approaches, linguistic and extralinguistic factors, L2 attrition, and heritage languages. The chapters summarize current research and draw on insights from related fields such as child language development, language contact, language change, pathological developments, and second language acquisition.
Keywords: dept.wll; faculty_collection

Using the knowledge framework and genre pedagogy for technology-enhanced form-function project-based language learning - Gleason, Jesse; Link, Stephanie (Global perspectives on project-based language learning, teaching, and assessment: Key approaches, technology tools, and frameworks, 2019)
Keywords: dept.wll

Online teacher training using the knowledge framework and teaching-learning cycle for literacy development - Link, S; Gleason, Jesse (Social Practices in Higher Education: A Knowledge Framework Approach to Linguistic Research and Teaching, 2019)
Keywords: dept.wll; faculty_collection

Promoting social justice with CALL - Gleason, Jesse; Suvorov, Ruslan (CALICO Journal, 2018)
Keywords: dept.wll; peer-reviewed

Farewell to Naples: Ferrante’s 'Story of a New Name' - Palma, Pina (Forum Italicum: A Journal of Italian Studies, 2018)
In Ferrante’s Story of a New Name, the protagonist’s journey to self-knowledge and self-realization is mapped through a farewell trip to Naples before she begins her studies in Pisa. As the centerpiece and background around and against which Elena’s accomplishments, failures, and societal pressures revolve, Naples emerges as a mosaic of energy and lethargy, unbreakable traditions and negligible innovations. While these elements mirror the protagonist’s powerlessness in changing the “norms” to which she is expected to adhere, they also function as her spur to a steady shift toward self-understanding. In this article, I analyze the ways in which Ferrante’s use of the beauty and lure, corrosiveness and lethality of Naples parallel her discourse on the protagonist’s search for self-understanding, a process that will ultimately enable Elena, the protagonist, to find self-realization. © 2018, The Author(s) 2018.
Keywords: authorship; dept.wll; labyrinth; memory; peer-reviewed; reading; self-fulfillment; self-knowledge; urban space

Review of 'Ecological crisis and cultural representation in Latin America: Ecocritical perspectives on art, film and literature' - Flores, William (Hispania-a Journal Devoted to the Teaching of Spanish and Portuguese, 2018)
Keywords: dept.wll; peer-reviewed

The devil and the mirror: Pulci’s theology - Palma, Pina (Luigi Pulci in Renaissance Florence and Beyond, 2018)
Keywords: dept.wll

Connected classrooms: Videoconferencing in TESOL teacher preparation - Schmitt, Elena; Eilderts, Luke (International Journal of Teaching and Learning in Higher Education, 2018)
Keywords: dept.wll; peer-reviewed; ⛔ No DOI found

Abundant student output through teachers’ big questions: A study in curricular design and teacher training - Verplaetse, Lorrie Stoops; Ferraro, Marisa; Mazzaro, M (TESOL Press Engaging Resources for Research - Elementary, 2018)
Keywords: dept.cur; dept.wll

Class, generation, and gender in Esther Tusquets's Habíamos Ganado La Guerra: Reflections on the winning of the Spanish Civil War - Weng, Miaowei (Hispanófila, 2018)
Keywords: dept.wll; peer-reviewed

El silencio abyecto en la plaza del diamante - Weng, Miaowei (Boletín Redipe, 2018)
The article examines the gender roles imposed on women in Spain under the Franco regime. It revisits Mercè Rodoreda’s 1962 novel The Time of the Doves and deciphers the female protagonist’s silence in the context of the post-Civil War period. Drawing on Julia Kristeva’s conception of the abject, it explores how silence becomes informative of the protagonist’s mental resistance to the patriarchal imposition, the helplessness and powerlessness a common woman feels under the Franco regime, and the gradual growth of female subjectivity.
Keywords: dept.wll; peer-reviewed; ⛔ No DOI found

Patterns of oral choice and evaluation across secondary content areas. - Gleason, Jesse; Berg, Margaret A; Huang, Jingzi (Language and Education, 2018)
Our study focuses on Choice and Evaluation, two of Mohan's knowledge structures to uncover how teachers and students across content areas developed disciplinary knowledge through classroom talk. Participants included in-service teachers and their students in rural and urban secondary schools in the Eastern and Western US. Through Choice and Evaluation, we examined opportunities for students across four disciplines to build up their knowledge of content matter or field. Findings revealed that teachers of math and science built students' field knowledge through classroom exploration, eliciting Evaluation in dialogic patterns involving Choice, while social studies and language arts teachers helped students implicitly use Choice/Evaluation through projects based on their previous experiences. The essential role of student background knowledge in enabling participation across different types of oral exchanges is shown. This study uncovers tendencies across classrooms and makes linguistically informed suggestions for teachers in the disciplines.
Keywords: Teacher education; classroom discourse; dept.wll; language across content; peer-reviewed

Evaluating teacher tech literacies using an argument-based approach - Gleason, Jesse; Schmitt, Elena (Assessment across online language education, 2018)
Keywords: dept.wll

Inclusive pedagogy for English language learners: A handbook of research-informed practices - Verplaetse, Lorrie Stoops; Migliacci, Naomi (Routledge, 2017)
In this Handbook leading researchers, teacher educators, and expert practitioners speak to current and future educators and educational leaders in understandable language about the research that informs best practices for English language learners integrated into the K-12 public school system. Responding to current state and federal mandates that require educators to link their practices to sound research results, it is designed to help educators to define, select, and defend realistic educational practices that include and serve well their English language learning student populations.  A critical and distinctive feature of this volume is its non-technical language that is accessible to general educators who have not been trained in the fields of second-language development and applied linguistics. Each chapter begins with a thorough discussion of the recommended practices, followed by a description of the research that supports these practices. The rigor of reported research is contained, but this research is written in a lay person’s terminology, accompanied by bibliographies for readers who wish to read about the research in technical detail. The volume is structured around four themes:• In the Elementary Classroom• In the Middle and Secondary Classroom• School and Community Collaboration• School and District Reform. Inclusive Pedagogy for English Language Learners is intended for current and future educational administrators, all educators who have a keen interest in school reform at the classroom, school, or district level, and staff developers, policy makers, parents and community groups, and anyone interested in the successful education of linguistically and culturally diverse students.
Keywords: dept.wll

Emerging second language writing identity and complex dynamic writing - Tu, I-Ju (Journal of World Languages, 2017)
Keywords: dept.wll

Review of 'Ethics of life: contemporary Iberian debates' - Flores, William (Hispania-a Journal Devoted to the Teaching of Spanish and Portuguese, 2017)
Keywords: dept.wll; peer-reviewed

Soldier-poet or écrivain-combattant: How the French trenches of World War I defined witnessing - Gleisner, Nichole T. (Studies in 20th & 21st Century Literature, 2017)
Keywords: dept.wll

Patterns of tasks, patterns of talk: L2 literacy building in university Spanish classes - Gleason, Jesse; Slater, Tammy (Language, Culture and Curriculum, 2017)
Second language (L2) classroom research has sought to shed light on the processes and practices that develop L2 learners' abilities [Nunan, D. 2004. Task-based language teaching. London: Continuum; Verplaetse, L. 2014. Using big questions to apprentice students into language-rich classroom practices. TESOL Quarterly, 179, 632-641; Zeungler, J., & Mori, J. 2002. Microanalyses of classroom discourse: A critical consideration of method. Applied Linguistics, 23(3), 283-288]. Honing in on the micro-level of classroom tasks and even further into the language of the tasks can help to reveal the patterns in teacher- and student-talk that help scaffold students' academic literacy. Literacy, from a systemic functional view of language learning, entails having the tools to function in the social contexts that are valued in students' lives. This study illustrates how grounded ethnography was used in conjunction with functional discourse analysis to illuminate bi-literacy development in two third-year university Spanish writing classes. Findings uncovered unique patterns of tasks and oral interactions that helped build students' academic bi-literacy. While grammar tasks helped build students' knowledge of wording-meaning relationships, culture and writing tasks supported their evolving understanding of how language construes content. This study puts forth a systemic functional curricular model for literacy-based tasks that aims to bridge the previously observed language-content gap.
Keywords: Language learning tasks; academic literacy; blended learning; classroom discourse; dept.wll; systemic functional linguistics; third-year Spanish courses

Ghost returns and historical memories in Zhang Yimou's Gui lai and Pedro Almodóvar's Volver - Weng, Miaowei (Canadian Review of Comparative Literature / Revue Canadienne de Littérature Comparée, 2017)
Keywords: dept.wll

Book Review: The labor of literature: democracy and literary culture in modern Chile. by Jane D. Griffin. Amherst and Boston: U of Massachusetts p, 2016, p. 218, 25.95/85.00. - Cardone, Resha Sophia (The Latin Americanist, 2017)
Keywords: book.review; dept.wll

Poesía concreto: Vuelta o la ciudad de México petrificada - Hernandez, Rafael (Revista Boletín Redipe, 2017)
Keywords: dept.wll; ⛔ No DOI found

La magia del amor, los horrores de la muerte y otros temas en los cuentos de Gabriel García Márquez - Pelayo, Ruben (Revista Boletín Redipe, 2017)
Keywords: dept.wll; ⛔ No DOI found